El Excentrico, 1954-06-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
June 5, 1954 [5 de junio de 1954]. Ano 4, No. 15. Cover has a phot of Eduardo Roybal, a candidate for Lt. Governor. This cover serves as a flyer encouraging viewers to vote him for Lt. Governor on June 8. The headline reads, "Take advantage of your privilege and rights--Vote June 8th."